KONFLIK NORMA DALAM PEMBERIAN IZIN JANGKA WAKTU HAK ATAS TANAH WILAYAH IBU KOTA NUSANTARA - Maulana, Muhammad Asrul; Sukardi; Salman, Radian (Veritas et Justitia, 2025)
This study analyzes the normative conflicts surrounding the regulation of land rights duration in Indonesia’s Capital City and the legal implications of the land rights cycle in its development. The research focuses on the implementation of Presidential Regulation Number 75 of 2024 and Government Regulation Number 29 of 2024, which amends Government Regulation Number 12 of 2023. Employing a normative method, the study reveals that inconsistencies arise between the general principles of the Basic Agrarian Law (UUPA) and the more specific provisions applicable to the Capital City. The newly introduced government regulation substantially extends the durations for the Right to Cultivate (HGU), Right to Build (HGB), and Right to Use, departing from UUPA’s more restrictive agrarian policies. This discrepancy creates legal uncertainty for investors and land users, underlining the urgent need for regulatory harmonization to maintain legal coherence and stability. Moreover, the policy allowing land control for up to two cycles may lead to monopolization and exacerbate social inequality due to the prolonged periods of HGU and HGB. The regulation also broadens foreign investor access to land in the Capital City, potentially clashing with UUPA’s principles of social justice and national sovereignty. To safeguard public interest, prevent legal ambiguity, and ensure equitable land governance, it is essential to align these new regulations with the foundational values of the UUPA. The government must provide a clear and accurate interpretation of these provisions and enforce limitations on land ownership by individuals and legal entities to prevent misuse and protect national interests.